The C3-H Bond Functionalization of Quinoxalin-2(1H)-Ones With Hypervalent Iodine(III) Reagents - Tan, Yushi; Wang, Jiabo; Zhang, Hong-Yu; Zhang, Yuecheng; Zhao, Jiquan (Frontiers in Chemistry, 2020)
The modification of quinoxalin-2(1H)-ones via direct C-H bond functionalization has recently received widespread attention, due to the quinoxalin-2(1H)-one derivatives’ various biological activities and pharmaceutical properties. This mini review concentrates on the accomplishments of arylation, trifluoromethylation, alkylation and alkoxylation of quinoxalin-2(1H)-ones with hypervalent iodine(III) reagents as reaction partners or oxidants. The reaction conditions and mechanisms are compared and discussed in detail.